Investigating the stability of meridionally and vertically varying ocean currents near the equator - Rees, J (2024)
To understand the instability mechanisms resulting in the generation of tropical instability waves (TIWs) and to explore the transport properties of finite amplitude waves, we investigate the stability of equatorial zonal flow profiles that are motivated by those obtained in both medium and high resolution eddy-resolving coupled atmosphere-ocean general circulation model integrations. We solve the linearised equations of motion for mean profiles characteristic of active time periods with regards to TIW growth. The fastest growing instability has wavelength of ~1000 km and a period of ~30 days. TIW growth is dominated by baroclinic production associated with the meridional temperature gradient north of the equator between the cold upwelled equatorial water and the warm off-equatorial water of the northern equatorial countercurrent (NECC). Utilising a fully nonlinear idealised three-dimensional zonally periodic channel in the NEMO ocean model initialised with identical mean fields as the linear model, we are able to explore the properties of TIWs throughout their life-cycle from early (linear) growth to decay. In this model, TIWs develop with wavelengths and periods of 930 km and 37.5 days, respectively. In agreement with the linear model, the early stage of TIW development is dominated by baroclinic production. However, as the TIWs equilibrate, they are dominated by a barotropic source and sink located on the northern and southern flanks of the equatorial undercurrent (EUC), respectively. The nonlinear model indicates that the net effect of TIWs on the mean fields is to decelerate the northern branch of the southern equatorial current (SECN), warm the surface equatorial waters associated with the equatorial cold tongue (ECT), and cool the subsurface northern waters associated with the NECC. Investigation of the terms in the eddy stress tensor elucidates the impact of TIWs on the mean flow. Eddies associated with TIWs act to flux eastward momentum into the SECN which decelerates the current, weakens its meridional and vertical shear, and therefore weakens the sources of barotropic and baroclinic instability from which TIWs derive their eddy energy. Employing a geometric decomposition of the eddy stress tensor allows us to interpret eddy feedbacks onto the mean flow via the spatial distribution of eddy ellipses. Horizontal eddy tilts, moving from the EUC to the SECN, exhibit a "banana-shape" which is indicative of an eastward momentum flux convergence into the southern flank of the SECN. Eddy tilts are also consistent with linear stability theory - tilting into the shear of the mean flow to extract energy from the mean state. Understanding the origin of the instability, and the transports associated with the eddies, could allow one to adjust parametrisations based on GEOMETRIC for better representation of TIWs in coarse resolution eddy-permitting coupled atmosphere-ocean general circulation models.